Real-World Data of Anticoagulant Treatment in Non-valvular Atrial Fibrillation - Calderon, Jose Miguel; Martinez, Fernando; Diaz, Javier; Fernandez, Antonio; Sauri, Inmaculada; Uso, Ruth; Trillo, Jose Luis; Vela, Sara; Bea, Carlos; Redon, Josep; Forner, Maria Jose (Frontiers in Cardiovascular Medicine, 2022)
Aims To assess the impact of anticoagulant treatment on risk for stroke and all-cause mortality of patients with atrial fibrillation using real-world data (RWD). Methods Patients with prevalent or incident atrial fibrillation were selected throughout a study period of 5 years. Stroke, transitory ischemic attack, hemorrhagic stroke, and all-cause mortality were identified in the claims of the electronic health records (EHRs). Subjects were classified according to the anticoagulant treatment in four groups: untreated, vitamin K antagonists (VKAs), New Oral Anticoagulants (NOACs), and antiplatelet (AP). Risk of events and protection with anticoagulant therapy were calculated by Cox proportional hazard models adjusted by potential confounders. Results From a total population of 3,799,884 patients older than 18,123,227 patients with incident or prevalent atrial fibrillation (AF) were identified (mean age 75.2 ± 11.5 years old; 51.9% women). In a follow-up average of 3.2 years, 17,113 patients suffered from an ischemic stroke and transitory ischemic attack (TIA), 780 hemorrhagic stroke, and 42,558 all-cause death (incidence of 46, 8, 2, and 120 per 1,000 patients/year, respectively). Among CHA2DS2, VASc Score equal or >2, 11.7% of patients did not receive any anticoagulant therapy, and a large proportion of patients, 47%, shifted from one treatment to another. Although all kinds of anticoagulant treatments were significantly protective against the events and mortality, NOAC treatment offered significantly better protection compared to the other groups. Conclusion In the real world, the use of anticoagulant treatments is far from guidelines recommendations and is characterized by variability in their use. NOACs offered better protection compared with VKAs.